Application of the Modified Exponential Function Method to the Cahn-Allen Equation - Bulut, Hasan (Amer Inst Physics, 2017)
In this study, we have applied the modified exp (-ohm(xi))-expansion function method to the Cahn-Allen equation. We have obtained some new analytical solutions such hyperbolic function solutions. Then, we have constructed the two and three dimensional surfaces for all analytical solutions obtained in this paper by using Wolfram Mathematica 9.
11th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 04-08, 2016 -- Univ La Rochelle, La Rochelle, FRANCE
Keywords: Traveling-Wave Solutions; (G'/G)-Expansion Method; Sumudu Transform; Complex